The Effect of Circuit Training on Increasing Physical Fitness of Class VIII Students of SMPN 1 Metro - Riyan Jaya Sumantri; Mikkey Anggara (Universitas Negeri Semarang, 2022)
Abstrak. In this research, the writer wanted to know the effect of circuit training on increasing physical fitness of class VIII students at SMPN 1 Metro, with a population of 140 students. The sample taken as much as 20% of the population is 30 students. The sampling method is a simple random sample. Exercise activities were carried out for 1.5 months with a frequency of exercise 3 times a week. The circuit training program that was tried was running back and forth with a distance of 4 m with 3 repetitions, putting the ball into the ring trying 5 times the ball entered the ring, running back and forth by observing the sound of the whistle, push ups 15